PERAN AKAL DALAM DALAM MEMAHAMI TEKS (NASH) DALAM BINGKAI MAQASHID AL-SHARYI’AH - Muhamad Zamroji; Ali Muchasan (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2020)
The results of this study prove that the framework of thought offered by 'Maqashid al-Sharyi'ah scholars regarding the protection of reason (hifzdu al-'aql) in terms of the practice of determining Maqashid al-Sharyi'ah, cannot be separated from the sharing of hifzdu al. -'aql in terms of maintaining its sustainability (min janib al-wujud) and hifzdu al-'aq l from the side of threats that can damage it (janib al-'adam) so that it contributes and the spirit empowers and maximizes intellectual potential in line with Maqashid al-Sharyi 'Ah. In addition, there is a close connection and relationship between protection of reason (hifzdu al-'aql) and Maqashid al-Sharyi'ah. This can be proven by how the role of punishment with reason for text (nash), the relationship of reason in understanding the text, universal (kulliyah) shar'iyah and 'aqliyah, and the neutrality of reason in syar’i. From the above explanation, it appears that Maqashid al-Sharyi'ah which is an axiology of Islamic law is an epistemology so that it becomes an independent scientific discipline. Thus Maqashid al-Sharyi'ah is able to dialectic with the problems of contemporary law that are always developing.